Notice that the graph appears to be a hyperbola which is asymptotic to
the line y = 1 (drawn in green). We shall now try different values of c
in order to see how this parent graph is altered.
Notice that the parent graph xy = x + y is shown in red, xy = x + y +
1 is shown in green, and xy = x + y + 3 is shown in blue. We should note
that all three graphs are asymptotic to the line y = 1 as well as the line
x = 1. It is easily seen from the graph that xy = x + y crosses the y-axis
at 0, xy = x + y + 1 crosses the y-axis at -1, and xy = x + y + 3 crosses
the y-axis at -3. We are also able to examine the equations xy = x + y -
3 (shown in purple) and xy = x + y - 4 (shown in aqua). This time, we see
that xy = x + y - 3 crosses the x-axis at 3 and it crosses the y-axis at
3. Furthermore, xy = x + y - 4 crosses the x-axis at 4 and it crosses the
y-axis at 4. These graphs, as the ones before, are also asymptotic to the
lines y = 1 and x = 1. At this point, it is possible to make several conjectures:
1) the graph of the equation xy = x + y + c is a hyperbola asymptotic to
y = 1 and x = 1;
2) If c > 0, the graph of xy = x + y + c crosses the y-axis at (-c);
3) If c < 0, the graph of xy = x + y + c crosses both the x-axis and
y-axis at c.
The graph of xy = x + y is shown in red, whereas the graph of xy = 2x
+ 2y is shown in green. The two graphs are similar in that they both cross
the y-axis at 0; however, they are different in that xy = x + y is asymptotic
to the line y = 1 and xy = 2x + 2y is asymptotic to the line y = 2 (shown
above in blue). Now, how does a constant transform the graph?
Let's treat each graph individually. The graph xy = 2x + 2y is shown
in green, is asymptotic to the graph graph y = 2 and x =2, and crosses the
y-axis at 0. The graph of xy = 2x + 2y + 1 is shown in red and crosses the
y-axis at -.5--which is one-half of the constant. The graph xy = 2x + 2y
+ 3 is shown in blue and crosses the y-axis at -1.5, and this is one-half
the constant. The graph of xy = 2x + 2y - 1 is shown in gold and crosses
the y-axis at .5. The graph of the equation xy = 2x + 2y - 3 crosses the
y-axis at 1.5. Once again, we may generalize:
1) The graph of xy = 2x + 2y is a hyperbola asymptotic to y = 2 and x =
2) If the equation xy = 2x + 2y + c, the graph crosses the y-axis at (-c/2).
Here, we see that the hyperbolas are all asymptotic to the lines y =
3 and x = 3. The red graph, green graph, and blue graph represent the equation
xy = 3x + 3y + c where c = 0 , c = 1, and c = 3, respectively. Similarly,
the gold graph and the purple graph represent the xy = 3x + 3y + c where
c = -1 and c = -3, respectively. As before, these graphs cross the y-axis
We have viewed enough graphs now to make several generalizations. Consider
the general form xy = ax + by + c, where a=b, and a, b, and c are real numbers.
will always graph as a hyperbola. The hyperbola is always asymptotic to
the lines x = a (or b) and y = a (or
of the graph may be obtained by the formula .
were to translate the origin to the point of intersection of the asymptotes
and consider the four quadrants, the
hyperbolas lie in the first and third quadrants. EXCEPTION: if a = b = 1
or if a = b = -1 and xy = ax + by + c and c < 0,
the hyperbola will lie in the second and fourth quadrants.
It appears as though our asymptotes will no longer be vertical and horizontal
because the graph seems to be "tilted," or "rotated."
Furthermore, students could be asked to explore the equations for the asymptotes,
make observations about x-intercepts and y-intercepts and then generalize,
and explore other values of a and b.
and determine under what conditions the relation is a hyperbola, or a
parabola, etc.. They could use the fact that the discriminant aids in making
Students could also explore several equations such as
and their graphs using a program such as Algebra Xpresser.